Cameroon : Ex Post Assessment of Longer-Term Program Engagement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Ex Post Assessment of Longer-Term Program Engagement for Cameroon highlights that the strengthening non-oil revenue and improving expenditure monitoring and control are critical to strengthening the fiscal position. Structural policies aimed at improving competitiveness and promoting private sector development, including by strengthening the financial sector, have been important to raise Cameroon's productive potential and generate employment. In both macroeconomic and structural policies, improving governance including through more transparency and accountability has been assigned a high priority.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet